PENGARUH MIGRASI TENAGA KERJA TERHADAP DINAMIKA PERDAGANGAN INTERNASIONAL DAN PEMBANGUNAN NASIONAL - Nafsi, Adibah Tazkiyyatun (Politeknik Negeri Lhokseumawe, 2025)
Abstract: Labor migration has become a global phenomenon influencing international trade dynamics and national development. This study aims to analyze the impact of labor migration on economic growth, trade balance, and human resource development in both origin and destination countries. The research employs a quantitative analysis method using secondary data from the World Bank and International Labour Organization (ILO), complemented by a literature review to identify trends and policy implications. The results indicate that labor migration positively contributes to the origin country's foreign exchange through remittances but also poses challenges such as brain drain. On the other hand, destination countries benefit from increased productivity and labor diversification. The conclusion emphasizes the need for balanced policies to maximize the benefits of migration while mitigating its negative impacts.Keywords: labor migration, international trade, national development, remittances, brain drain.